2004
DOI: 10.1111/j.0924-2708.2004.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal speech perception in schizophrenia with auditory hallucinations

Abstract: Our results support the claim that schizophrenic patients with AH are likely to have a disturbance of the speech perception system. Moreover, our data suggest that non-language attention might be a key factor influencing speech perception ability and that speech perception dysfunction might be a trait marker in schizophrenia with AH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
2
8
1
1
Order By: Relevance
“…Hence, depending on the severity of psychosis, we believe that sentences should be encouraged when assessing auditory function in schizophrenia patients. This is consistent with a study done by Lee et al 45 that found schizophrenia patients without auditory hallucination demonstrate relatively similar ability with healthy controls when listening to narrative text in low noise conditions. In addition, schizophrenia patients have more impairment in comprehending non-literal compared to literal sentences.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, depending on the severity of psychosis, we believe that sentences should be encouraged when assessing auditory function in schizophrenia patients. This is consistent with a study done by Lee et al 45 that found schizophrenia patients without auditory hallucination demonstrate relatively similar ability with healthy controls when listening to narrative text in low noise conditions. In addition, schizophrenia patients have more impairment in comprehending non-literal compared to literal sentences.…”
Section: Discussionsupporting
confidence: 93%
“…An investigation of speech perception ability using narrative texts embedded in phonetic noise has also been documented. 16 In addition, a study by Ross et al 17 also suggested that schizophrenia patients demonstrated no deficits in recognizing monosyllabic words in background noise. Another study using Speech-in-Babble Perception test, 18 however, revealed that patients with first-episode psychosis do have difficulties when listening to targeted signals embedded in noise.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia patients with hallucinations were not impaired on the nonlinguistic, auditory, continuous-performance task-suggesting that these deficits were specific to verbal working memory. Using a similar paradigm, Lee and colleagues 50 replicated the finding of impairment on a masked-speech tracking test. This impairment was still observed eight weeks later, well after the hallucinations subsided-suggesting that a speech-perception dysfunction may be a trait characteristic.…”
Section: Another Possible Account Of Avhs?mentioning
confidence: 86%
“…Studies have also looked at language production, speech production, and perception, rather than specifically at inner speech itself in patients who experience AVHs. The left superior temporal cortex, which supports linguistic functions, has consistently been reported to activate during auditory–verbal hallucinations in schizophrenia patients . Auditory verbal hallucinations have been shown to be related to defined cortical areas linked to specific language functions.…”
Section: Cognitive Neurobiological Modelsmentioning
confidence: 96%